Preventive Resin Restoration in Child Patients:A Serial Case Report - Laelia Dwi Anggraini; Rifqi Mutia Zahwa; Eva Febrian Saputri (International Conference on Economic Business and Social Science, 2024)
Dental caries is a significant global health challenge today because the pits and fissures in teeth provide an ideal place for bacteria and substrates that trigger caries. Preventive Resin Restoration (PRR) is an effective secondary prevention solution to stop the development of caries lesions. In the first case, a 4 year old girl complained of black lower right back teeth. The planned maintenance is IEC, PRR, and periodic control. The second case involved a 13 year old girl who complained of a white spot on her lower right back tooth. In this case, PRR Type A was chosen as the appropriate treatment. PRR, which involves using resin to fill damaged tooth tissue and sealing pits and fissures with a sealant, has been proven effective in restoring caries in these areas and preventing further progression. There are three different types of PRR (Type A, Type B, and Type C), with resin-based sealant being one of the main materials used because of its good retention resistance. The use of PRR is not only effective in treating caries cases, but also as a preventive measure to prevent pit and fissure caries in the future. It is important to follow the treatment protocol systematically, undergo regular check-ups, and maintain dental hygiene to ensure the success of the restoration and prevent further caries. Thus, PRR is an efficient and effective solution in the management of dental caries and prevention of related oral health problems.